Benefits of plant cell suspension to vesicular-arbuscular mycorrhizal fungi in vitro. I. Effects of plant species and cell suspension age. - Paula, Mauro Augusto de; Siqueira, José Oswaldo; Pinto, José Eduardo Brasil Pereira; Pasqual, Moacir (Pesquisa Agropecuaria Brasileira, 2014)
The effects of addition of cell suspension on germination, rate and micelial growth of vesicular-arbuscular mycorrhizal fungi spores in vitro were studied, aiming to establish monoxenous culture and sporulation of these fungi in the absence of living roots. Application of lucerne, potato, sweet potato, pueraria and tomato plant cells into agar-plates containing desinfested azygospores of Gigaspora margarita, Gigaspora gigantea and Scutellospora heterogaina, increased azygospore germination and favoured their gemi tubo growth. The beneficial effects were maximum when six-day old pueraria cells were utilized. These cells stimulated micelial growth by as much as 200%, over the no cells control However, neither hyphal growth was directed towards the plant cells nor visual signs of cell colonization by the hyphae or fungal sporulation were observed.